Spectral Analysis of the Relation between Gross Employment Changes and Output Changes, 1958-1966 - Hamermesh, Daniel S. (The Review of Economics and Statistics, 1969)
T HIS paper has the dual purpose of presenting spectral analysis in a different, perhaps more appropriate application than that of past work and of analyzing differences among industries in the relation of gross changes in employment and changes in output. Spectral analysis has been applied to a problem in labor economics only once.' The cause of the dearth of studies using the technique is possibly the limited number of observations available on most variables relating to labor. Even if we had such information, there are relatively few problems for which spectral analysis might be expected to give interesting results. The technique does not seem to have produced much new evidence about the cyclical relationships to which it has been applied, perhaps because we have so few observations on complete cycles in economic activity, or perhaps because these low-frequency movements are of such irregular length as to be undetectable by spectral analysis.2 Because of these problems the major use of this technique in labor economics must lie in the analysis of behavior reflected at higher frequencies, particularly to those we call seasonal. It is only at those frequencies that we have enough information on behavior to make any inferences about it.